2012
DOI: 10.3389/fpls.2012.00031
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Plant P-Type ATPases

Abstract: Five organisms having completely sequenced genomes and belonging to all major branches of green plants (Viridiplantae) were analyzed with respect to their content of P-type ATPases encoding genes. These were the chlorophytes Ostreococcus tauri and Chlamydomonas reinhardtii, and the streptophytes Physcomitrella patens (a non-vascular moss), Selaginella moellendorffii (a primitive vascular plant), and Arabidopsis thaliana (a model flowering plant). Each organism contained sequences for all five subfamilies of P-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
98
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 92 publications
5
98
0
Order By: Relevance
“…It plays an important bioenergetics and regulatory function in plant cell physiology (Polevoi, 1986;Gaxiola, Palmgren, and Schumacher, 2007). The structure and evolution of the PM proton pump are well documented (Pedersen et al, 2007(Pedersen et al, , 2012. The protein consists of six transmembrane domains, two cytosolic loops and a long C-terminal domain (rev.…”
Section: Regulation Of Plasma Membrane H + -Atpase At Post-translatiomentioning
confidence: 99%
“…It plays an important bioenergetics and regulatory function in plant cell physiology (Polevoi, 1986;Gaxiola, Palmgren, and Schumacher, 2007). The structure and evolution of the PM proton pump are well documented (Pedersen et al, 2007(Pedersen et al, , 2012. The protein consists of six transmembrane domains, two cytosolic loops and a long C-terminal domain (rev.…”
Section: Regulation Of Plasma Membrane H + -Atpase At Post-translatiomentioning
confidence: 99%
“…The genome of higher plants encodes several Ca 2+ -ATPases which group either with animal sarco-endoplasmic reticulum Ca 2+ -ATPase in the 2A subgroup of P-type ATPases (ECA, E R-type C a 2+ - A TPase) or with animal plasma membrane (PM) Ca 2+ -ATPase in the 2B subgroup (ACA, a uto-inhibited C a 2+ - A TPase). Arabidopsis ( Arabidopsis thaliana ) has four ECA and ten ACA genes, with most cells expressing multiple isoforms (Geisler et al 2000a; Sze et al 2000; Bonza and De Michelis 2011; Pedersen et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…In previously characterized members of the ACA subgroup, the N-terminus has been found to have an auto-inhibitory domain and a partially overlapping high affinity calmodulin (CaM) binding site (Geisler et al 2000a; Baxter et al 2003; Kabala and Klobus 2005; Boursiac and Harper 2007; Bonza and De Michelis 2011; Pedersen et al 2012); a second low affinity CaM-binding site has been recently identified just 8 aa downstream the first one in ACA8, one of the best characterized ACA isoform (Tidow et al 2012). In all ACA isoforms characterized so far, CaM-binding suppresses the auto-inhibitory action of the N-terminus, increasing V max and decreasing K 0.5 for free Ca 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…With its electroneutral function, a Na + / H + antiporter cannot perform Na + efflux under high pH conditions, whereas Na + /K + -ATPase and ENA ATPase are ΔpH-independent and thus they can mediate Na + efflux under alkaline pH conditions (Garciadeblas et al 2001;Rodríguez-Navarro and Benito 2010). Genome sequence information has revealed the loss of Na + -ATPase in vascular plants during evolution in fresh water environments (Graciadeblas et al 2001;Pedersen et al 2012), and the existence of Na + /K + -ATPase and/or ENA ATPase in eukaryotes living in highly alkaline and saline environments such as the sea was proposed.…”
mentioning
confidence: 99%
“…Eukaryotes possess a P-type ATPase as a primary pump on the plasma membrane, which can play essential roles in the homeostasis of intracellular Na + concentrations (Palmgren and Nissen 2011;Pedersen et al 2012). There are three kinds of P-type ATPase related to Na + efflux across the plasma membrane; Na + /K + -ATPase in animal cells, H + -ATPase in plant and fungal cells and ENA ATPase found in bryophytes and protozoa.…”
mentioning
confidence: 99%